Characterization of defensin gene of Asom hill goat and in-silico designing of novel antimicrobial peptides - BHARALII, KRISHNA; KALITA, D J; BORA, P; SAIKIA, D P; DEVI, B; DAS, L (The Indian Journal of Animal Sciences, 2018)
Tissue samples of tongue were collected from apparently healthy Asom hill goat from local slaughter house. Total RNA was extracted and reverse transcribed to cDNA. Size of the amplified products of defensin gene with specific primer were 266 bp. Positive clones were sequenced and analyzed using DNA Star software. At nucleotide level, the Asom hill goat LAP cDNA showed a variation of two nucleotides at 37 and 194 with Capra hircus LAP. Nucleotide sequence of Asom hill goat LAP showed highest similarity of 99% with Capra hircus LAP followed by 95.4% with Capra hircus EBD and 91.3% with sheep BD2. The predicted peptide of Asom hill goat LAP comprised 64 amino acids. Analysis of mature domain of Asom hill goat LAP revealed the presence of 13 basic, 20 hydrophobic, 3 proline and 1 histidine amino acid. Support Vector Machine (SVM) algorithm was used for designing and prediction of antimicrobial potency and amino acids in between 25-39 of mature domain of Asom hill goat LAP predicted to be most potent among all the designed peptide.